PENGARUH GUIDED DISCOVERY LEARNING BERBANTUAN MEDIA ARTICULATE STORYLINE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN GEOGRAFI - Rivaldi, Cintya Fandani; Sahrina, Alfi; Rosyida, Fatiya; Wiwoho, Bagus Setiabudi (Universitas Negeri Malang, 2024)
THE EFFECT OF ARTICULATE STORYLINE ASSISTED GUIDEDDISCOVERY LEARNING ON STUDENTS' CRITICAL THINKING ABILITY INLEARNING GEOGRAPHY Critical thinking is a skill that must be honed and developed in 21st-century learning because it isuseful in studying and solving problems that arise. Based on its advantages, the Guided DiscoveryLearning model is able to improve the ability to think critically. On the other hand, the use ofarticulate storyline media is able to clarify the information or message conveyed so that it canfacilitate the learning process. The purpose of this study was to determine the effect of GuidedDiscovery Learning assisted by articulate storyline media on students' critical thinking skills ingeography learning. The research design used a Quasi-Experimental design with a post-test-onlygroup design. The research subjects included students of grade X5 and grade X6, withexperimental class (class X5) and control class (class X6). The determination of the class is doneby means of Random Sampling through a lottery. The results showed that the mean value of thepost-test of critical thinking skills of experimental class students with Guided Discovery Learningmodel treatment assisted by articulate story media was higher (86.09) than the control class(79.87). The results of hypothesis testing with an independent sample test showed a significancevalue of 0.000 less than 0.05. These results prove that the Guided Discovery Learning model,assisted by articulate storyline media, has a positive impact on students' critical thinking skills.There are other findings in this study, namely the stimulus and proof stages as the most dominantstages affecting critical thinking skills. Pemikiran yang kritis menjadi suatu keterampilan yang harus diasah dan dikembangkan dalampembelajaran abad 21, karena berguna dalam mengkaji dan menyelesaikan permasalahan yangmuncul. Berdasarkan keunggulan yang dimilikinya, model Guided Discovery Learning mampumeningkatkan kemampuan untuk berpikir kritis. Disisi lain, penggunaan media articulate storylinemampu memperjelas informasi atau pesan yang disampaikan, sehingga dapat memperlancarproses pembelajaran. Tujuan penelitian ini yaitu untuk mengetahui pengaruh Guided DiscoveryLearning berbantuan media articulate storyline terhadap kemampuan berpikir kritis bagi siswapada pembelajaran geografi. Desain penelitian menggunakan rancangan Quasi Experimentalwith post-test only group design. Adapun subjek penelitian meliputi siswa kelas X5 dan kelas X6,dengan kelas eksperimen (kelas X5) dan kelas kontrol (kelas X6). Penentuan kelas tersebutdilakukan dengan cara random sampling melalui undian. Hasil penelitian menunjukkan bahwanilai rerata post-test kemampuan berpikir kritis siswa kelas eksperimen dengan perlakuan model Guided Discovery Learning berbantuan media articulate storyline lebih tinggi (86.09)dibandingkan kelas kontrol (79.87). Hasil uji hipotesis dengan independent sample testmemperlihatkan nilai signifikansi sebesar 0.000 kurang dari 0.05. Hasil tersebut membuktikanbahwa model Guided Discovery Learning berbantuan media articulate storyline berpengaruhterhadap kemampuan berpikir kritis siswa. Terdapat temuan lain pada penelitian ini, yaitu tahapanstimulus dan pembukt